Jute sticks derived novel graphitic porous carbon nanosheets as Li‐ion battery anode material with superior electrochemical properties. (5th December 2019) - Nanaji, Katchala; Rao, Tata Narasinga; Varadaraju, UV; Anandan, Srinivasan
Summary: Graphitic porous carbon sheets (GPCS), which were synthesized at a low temperature of 900°C by KOH chemical activation technique, possess a specific surface area of 1246 m 2 g ‐1 with high pore volume. The size of the pores varied in micro‐mesopore regions and exhibited three‐dimensional sheet‐like morphology composed of multilayered graphene sheets with an inter planar distance of 0.360 nm. The GPCS material was tested as anode for Li‐ion battery (LIB) application in half cell mode (vs Li + /Li). The fabricated GPCS electrode shows excellent electrochemical properties in comparison with commercial graphite such as a high discharge specific capacity of 1022 mA h g ‐1 after 10 cycles at 100 mA g ‐1 and excellent specific capacity retention of 170 mA h g ‐1 at a very high current rate of 8000 mA g ‐1 and also retains a high capacity of 541 mA h g ‐1 after 250 cycles at 500 mA g ‐1, which suggests that GPCS material can be a promising electrode for LIB application. A brief comparison with commercial graphite and various carbonaceous materials from literature demonstrated that the GPCS electrode was potential material for high rate LIBs. Abstract : Graphitic porous carbon nano sheets are synthesized from jute stick bio‐waste by simple chemical activation at low temperature of 900 o C For Li‐ion battery application, GPCS delivers a high discharge specific capacity of 1022 mA h g ‐1 at 100 mA g ‐1 Excellent rate capability of 170 mA h g ‐1 at a very high current density of 8000 mA g ‐1 Good cyclic stability of 541 mA h g ‐1 after 250 cycles at 500 mA g ‐1 Improved electrochemical properties using a bio‐waste derived carbon in comparison to commercial graphite